A new type of ferrocene-based phosphine-tert-butylsulfinamide ligand: synthesis and application in asymmetric catalysis1. Issue 45 (20th May 2015) - Ma, Jiangwei; Li, Chuang; Zhang, Dongxu; Lei, Yang; Li, Muqiong; Jiang, Ru; Chen, Weiping
<x xml:space="preserve">Abstract</x> The first example of P, S-bidentate ligands containing both a planar chiral scaffold and a chiral sulfinamide moiety were reported.